Financing the 2000 election - Magleby, David B.; Brookings Institution (Washington, D.C. : Brookings Institution Press, 2002)
A series of 10 papers, presented by Magleby (Center for the Study of Elections and Democracy, Brigham Young U.), explore the money issues behind the American political campaigns of 2000. Patterns of campaign spending, strategies of funding campaigns, patterns of change across different political organizations, and other broad issues are discussed in early chapters, while later contributions delve into the particulars of the financing of the presidential nominations, the general presidential election, the spending of interest groups, and congressional campaigns. The material focuses on the Republicans and the Democrats, although there is some very brief discussion of the campaigns of Pat Buchanan, Ralph Nader, and other third party candidates. Annotation copyrighted by Book News, Inc., Portland, OR.
Foreword -- Acknowledgments -- 1. A high-stakes election / David B. Magleby -- 2. Spending in the 2000 elections / Candice J. Nelson -- 3. The 2000 presidential nominations : the costs of innovation / John C. Green and Nathan S. Bigelow -- 4. Financing the 2000 presidential general election / Anthony Corrado -- 5. Financing the 2000 Congressional elections / Paul S. Herrnson and Kelly D. Patterson -- 6. Throwing out the rule book : party financing of the 2000 elections / Diane Dwyre and Robin Kolodny -- 7. Interest groups and financing the 2000 elections / Allan J. Ciglar -- 8. Financing gubernatorial and state legislative elections / Anthony Gierzynski -- 9. Financing judicial elections / Roy A. Schotland -- 10. Lessons for reformers / Thomas E. Mann -- Contributors -- Index.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: United States. -- Congress -- Elections, 2000 -- Finance; United States. -- Congress; Campaign funds -- United States; Presidents -- United States -- Election -- 2000 -- Finance; United States -- Politics and government -- 1993-2001.; États-Unis -- Politique et gouvernement -- 1993-2001.; POLITICAL SCIENCE -- Political Process -- General; BUSINESS & ECONOMICS -- Public Finance; Campaign funds; Politics and government; Presidents -- Election -- Finance; United States; Verkiezingsfondsen; Presidenten; Verenigde Staten; 1993-2001